Investigating the Links between Radio Pulsar Populations that Display Intermittent Emission Phenomena at Low Frequencies - Meyers, Bradley Ward (Curtin University, 2019)
Pulsars are unparalleled astrophysical tools, yet, after more than 50 years of research, we still do not fully understand the mechanism responsible for their radio emission. Through a series of systematic, simultaneous and wideband observations of three sporadically emitting pulsars, we have revealed the importance of low-frequency information when characterising the emission, and support the idea that the intermittent emission behaviour is likely due to the same physical mechanism operating on different time scales.